Astrocytes and Adenosine A2A Receptors: Active Players in Alzheimer’s Disease - Lopes, Cátia R.; Cunha, Rodrigo A.; Agostinho, Paula (Frontiers in Neuroscience, 2021)
Astrocytes, through their numerous processes, establish a bidirectional communication with neurons that is crucial to regulate synaptic plasticity, the purported neurophysiological basis of memory. This evidence contributed to change the classic “neurocentric” view of Alzheimer´s disease (AD), being astrocytes increasingly considered a key player in this neurodegenerative disease. AD, the most common form of dementia in elderly people, is characterized by a deterioration in memory and in other cognitive functions. Although, the early cognitive deficits have been associated with synaptic loss and dysfunction, caused by amyloid-β (Aβ), accumulating evidences support the role of astrocytes in AD. Astrocyte atrophy and reactivity occurring in early and later stages of AD, respectively, involve morphological alterations that translate into functional changes. However, it remains to be defined the main signals responsible for astrocytic alterations in AD and their impact on synaptic function. One possible candidate is adenosine, which can be derived the extracellular catabolism of ATP released by astrocytes. Adenosine can act as a homeostatic modulator and also as a neuromodulator at the synaptic level, through the activation of adenosine receptors, mainly of A1R and A2AR subtypes. These receptors are also present in astrocytes, being particularly relevant in pathological conditions, to control the morpho-functional responses of astrocytes. Here we will focus on the role of A2AR, since they are particularly associated with neurodegeneration and also with memory processes. Furthermore, A2AR levels are increased in the AD brain, namely in astrocytes where they can control key astrocytic functions. Thus, unveiling the role of A2AR in astrocytes function might might shed light on novel therapeutic strategies for AD.